Driving eco-innovation in supply chains through multi-stakeholder collaboration: A review and research agenda - Ana Inês; Andreia Diniz; António C. Moreira (Journal of Open Innovation: Technology, Market and Complexity)
This article examines the concept of eco-innovation (EI) and its role in achieving sustainable economic growth by integrating environmental and social considerations. It focuses on identifying key practices and relationships that promote EI in supply chains through multi-stakeholder collaboration. By systematically reviewing existing literature, the article highlights the challenges and opportunities of implementing eco-innovative practices. It emphasizes the importance of collaborative networks, including companies, suppliers, universities, governments and civil society, in facilitating EI within supply chains. The findings aim to assist firms and practitioners in comprehending the crucial concepts and relationships related to eco-innovation in supply chains. The article serves as a comprehensive overview of the importance of eco-innovation, the role of collaborative networks and multi-stakeholder engagement and the need to adopt a holistic approach to drive eco-innovative practices in supply chains for sustainable economic growth. Additionally, the article suggests potential areas for future research in this field.